KINERJA BADAN PENDAPATAN DAERAH KABUPATEN KAMPAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH - Irafeni, Ria; RFS, Harapan Tua (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to describe the performance carried out by the Regional Revenue Agency of Kampar Regency in increasing Regional Original Income (PAD) in Kampar Regency and the factors that influence this performance. This study uses a qualitative method which aims to provide an overview of the state of the object in accordance with the information and facts obtained in the field. Data collection techniques in this study were interviews and observation. Then the informants in this study were the Head of the Regional Revenue Agency of Kampar Regency, the Secretary of the Planning and Data Sub Division of the Regional Revenue Agency, and the Staff of the Regional Original Revenue. The results of the performance of the Kampar Regency Regional Revenue Agency in increasing Regional Original Income have not been optimal. This is caused by performance that has not reached the appropriate criteria, as well as the government's lack of sensitivity in exploring potential sources of local revenue. n addition, the low awareness of the public in paying taxes is also the reason the Kampar Regency's Original Revenue is not optimal. Then other factors that affect the performance of the Regional Revenue Agency of Kampar Regency are individual factors concerning the quality of the Human Resources in it and organizational factors including a conducive work atmosphere.                                                                                                                         Keyword: Performance, Locally-generated revenue